Think-Aloud-Based Translation Process Research: Some Methodological Considerations - Sun, Sanjun (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
Mainly structured around issues revealed in a questionnaire survey among 25 eminent translation process researchers worldwide, this paper deals with methodological issues in think-aloud-based translation process research from two perspectives: theoretical and practical. It argues that there is no strong evidence suggesting that TAP significantly changes or influences the translation process, though TAP’s validity and completeness in a specific study might depend more or less on several variables. TAP and such recording methods as keystroke logging and eye tracking serve different specific research purposes, so they can be combined in a multimethod study to answer more complex research questions. Several research designs are available for a multimethod study, and researchers are encouraged to try designs other than one-shot case studies or convergence design. As for the research procedure, this paper touches upon how to transcribe and analyze the protocols. Many stereotypes in this field have been problematized. For example, this paper suggests that researchers transcribe as much as necessary rather than doing a “complete” transcription, or they can even skip the step of transcribing; in choosing test materials, researchers do not have to choose whole passages; they can use a group of sentences.